Implicações do desenvolvimento agroindustrial na sustentabilidade ambiental: um estudo no estado do Mato Grosso - Redivo, Adriana Regina (2010)
Sustainable development has been extensively debated, and it is a matter of great concern for the agribusiness sector in Brazil, especially in the state of Mato Grosso, the largest soybean producing state in the country. This topic includes complex issues that ought to be considered as multidisciplinary. The process of action planning should encompass a broad systemic context that includes sustainability dimensions (environmental, economic, and social). This study evaluated the agribusiness production development of Mato Grosso state and identified impacts of its growth on the agroindustry. In order to evaluate the agribusiness development, technical base indicators such as credit evolution, soil occupation were defined, machinery and equipment, consumption of fertilizers and agroindustry development . The environmental indicators considered for the evaluation of the impacts of this development on the environment were agrochemicals, deforestation, and forest fire/hotspots. The methodology used was an explanatory qualitative research based on secondary sources. This study is a theoretical dissertation that focuses on agribusiness and stockbreeding development as well as the advances of the agroindustry in the state of Mato Grosso. The results indicate that the growth in grain production and the consumption of fertilizers, together with the increase in the credit limit and in the amount of machinery and equipment, are directly related to the environmental degradation in the state. Such fact was confirmed by the increase in the environmental indicators mentioned above and by the fact that the agroindustry has been standing out in the state. It can be said that, so far, the major concern of this sector has been production increase, and therefore, sustainable production, especially regarding environmental issues, is a secondary concern when different sustainability approaches for the agroindustry development are considered. This research indicates a need for change in the profile of the rural producer, mainly with regard to environmental issues, in order to achieve sustainability and guarantee that this industry sector will last for future generations.